"Significado que atribuyen las familias a la Atención de Salud. Distrito de Sanagoran-Huamachuco.2012" - Amador Monzon, Santos Milder (2013)
The present qualitative investigation of guy ethnographic he came true with families of the district of Sanagoran, Provincia of Sánchez Carrión, Región Freedom; During the months of December of the 2012 to February of the 2013 with the aim of determining the significance that the families for the attention of health attribute, four families, for the collection of data participated the ethnographic interview was used. The obtained information was processed and analyzed, intervening the ethnographic description, identification of controls, taxonomic analysis and analysis of themes and sub-themes, being the main theme: “There is bad attention with excessive bureaucratic step and our people have to receive cares plus a worthy deal ”, sub-themes were: I ) access is not easy it is difficult; Ii ) If he caters badly for The People you generate distrust and you lose approval and IAII ) The staff of health is indifferent to our problems. This indicates Dissatisfaction in attention, inopportune attention and I neglect in the comprehensive care the user, so that the staff of the Establishments of Salud is to modify his attitudes in the deal with these patients, that they have a based cultural identity in the Andean worldvision.